Decline, Transformation and Trust in Parliaments: the Portuguese Case in a Longitudinal and Comparative Perspective - Teixeira, Conceição Pequito; Freire, André (Revista Ibero-Americana de Estudos Legislativos, 2010)
In this article we will analyse trends in levels of trust in national parliaments across Europe and individual determinants for trust in the Spanish, Italian and Portuguese parliaments. To do so, we will integrate two theoretical and research perspectives that are not normally associated with studying parliamentary institutions. The first focuses on studying citizens’ attitudes and political behaviour to understand causes and consequences of the growing erosion of public support for democratic institutions. The second aims at studying the role of parliaments and is mainly concerned with the decline and transformation of legislatures. Given the more detailed and available empirical information for the Portuguese case, we will attempt to discover if the trust Portuguese citizens place in their parliament is associated with their views on its roles and functions. However, comparisons with the Spanish and Italian cases will also be done in this respect.